2017
DOI: 10.1111/aman.12845
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Patterns of Mexican Migrant Genetic Ancestry: Implications for Identification

Abstract: Motivated by the humanitarian crisis along the US-Mexico border and the need for more integrative approaches to migrant death investigations, we employ both biological and cultural anthropology perspectives to provide insight into these deaths and the forensic identification process. We propose that structural vulnerabilities linked to ethnicity impact the success of identifying deceased migrants. Using forensic genetic data, we examine the relationships among identification status, case year, and ancestry, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 49 publications
0
41
0
Order By: Relevance
“…To determine whether there exists a relationship between the nature of the FD3 misclassifications (the reference groups to which targets are assigned) and individual levels of continental—African, European, and Indigenous American—ancestry, we generated for all PCOME test samples their relative proportions, or percent, of African, European, and Indigenous American ancestry. These estimates were derived from traditional cranial measurement data following the procedures already described by Algee‐Hewitt for the inference of continental ancestry and the quantification of admixture among contemporary individuals of United States and Latin American origins at various geographic (country‐wide, regional, and state) scales. We applied the unsupervised model‐based clustering methods of finite mixture analysis to a matrix of 20 craniofacial shape measures for a sample of 2277 individuals.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine whether there exists a relationship between the nature of the FD3 misclassifications (the reference groups to which targets are assigned) and individual levels of continental—African, European, and Indigenous American—ancestry, we generated for all PCOME test samples their relative proportions, or percent, of African, European, and Indigenous American ancestry. These estimates were derived from traditional cranial measurement data following the procedures already described by Algee‐Hewitt for the inference of continental ancestry and the quantification of admixture among contemporary individuals of United States and Latin American origins at various geographic (country‐wide, regional, and state) scales. We applied the unsupervised model‐based clustering methods of finite mixture analysis to a matrix of 20 craniofacial shape measures for a sample of 2277 individuals.…”
Section: Methodsmentioning
confidence: 99%
“…The study of morphological variation in the cranium is a cornerstone of skeletal population analyses, with standard interlandmark distance (ILD) measurements, that is, traditional craniometric data, providing adequate information for revealing population structure and, in turn, speaking to population histories at various levels of specificity . In terms of their information on biogeographic ancestry, craniometrics can capture both broad continental variation that may reflect our evolutionary history, and the more nuanced regional variation that may signal recent micro‐evolutionary processes, such as admixture events .…”
mentioning
confidence: 99%
“…These results suggest, to some degree, regional population continuity throughout the colonial period. Other recent studies have focused on genetic variation of mestizos primarily for the purpose of forensic investigations (Hughes, Algee-Hewitt, Reineke, Clausing, & Anderson, 2017;Martínez-Cortés et al, 2017) and implications for drug treatment response (Favela-Mendoza et al, 2018). Research carried out by INMEGEN has been criticized for creating a bias in genomic research resulting from excessively high public and government expectations, with a major goal of the work to accommodate postrevolutionary ideas of a Mexican citizen (Beltran, Garcia Deister, & Rios, 2014).…”
Section: Genetic and Related Bioarcheological Studiesmentioning
confidence: 99%
“…2010; Simms et al, 2010;Scliar et al, 2009;Ibarra-Rivera et al, 2008;Ricaut et at., 2005;Rubi-Castellanos et al, 2009b;Kraaijenbrink et al 2014;Bosch et al, 2001). Additionally, more finegrained analyses for estimating levels of admixture in individuals have also successfully been produced (Juarez-Cedillo et al, 2008;Halder et al, 2009, Hughes et al, 2017. This breadth of work, including those studies of highly admixed individuals, implicitly speaks to the ability to use CODIS loci-selected for their ability to produce high individual identifiability-to produce information about genetic ancestry for individuals.…”
Section: Codis Panel: Applications and Researchmentioning
confidence: 99%
“…Over the last decade, a plethora of published data on population variation for CODIS STRs, particularly for Mexico Sánchez et al, 2005;González-Martín et al, 2008;Rubi-Castellanos et al 2009b;Quinto-Cortés et al, 2010;Rangel-Villalobos et al, 2013;Rangel-Villalobos et al, 2014;Martinez-Gonzalez et al, 2016) has made this research on geographic structure of genetic variations possible, with compelling inferences such as the asymmetric admixture patterns established for regions in Mexico (Rubi-Castellanos et al, 2009a). Beyond population demographic studies, the nontraditional application of CODIS loci as admixture inference-markers has also led to the recognition of ancestry-based biases in the identification process of unidentified deceased border crossers along the U.S.-Mexico border, which found that the potential of a positive identification was related to the amount of European admixture of the individual being investigated (Hughes et al, 2017).…”
mentioning
confidence: 99%